2005
DOI: 10.1530/rep.1.00452
|View full text |Cite
|
Sign up to set email alerts
|

Effect of genetic background and activating stimulus on the timing of meiotic cell cycle progression in parthenogenetically activated mouse oocytes

Abstract: With the aim of investigating the effects of oocyte genotype and activating stimulus on the timing of nuclear events after activation, oocytes collected from hybrid B6D2F1, inbred C57BL/6 and outbred CF-1 and immunodeficient nude (NU/1 ) females were activated using ethanol or strontium and fixed at various time-points. Meiotic status, spindle rotation and second polar body (PB2) extrusion were monitored by fluorescence microscopy using DNA-, microtubule-and microfilament-selective probes. Although activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…In our preliminary experiments, we have confirmed the difficulty in activating 129 strain oocytes by strontium: many of them arrested at metaphase II (35%, 6/17) or metaphase III (47%, 8/17), and only 18% (3/17) developed to 2-cells (unpublished). Although it was reported that C57BL/6 strain oocytes also often arrested at metaphase III after parthenogenetic development [42], ROSI-generated embryos in this study developed into 2-cell embryos at normal rates (45–89%).…”
Section: Discussionmentioning
confidence: 52%
“…In our preliminary experiments, we have confirmed the difficulty in activating 129 strain oocytes by strontium: many of them arrested at metaphase II (35%, 6/17) or metaphase III (47%, 8/17), and only 18% (3/17) developed to 2-cells (unpublished). Although it was reported that C57BL/6 strain oocytes also often arrested at metaphase III after parthenogenetic development [42], ROSI-generated embryos in this study developed into 2-cell embryos at normal rates (45–89%).…”
Section: Discussionmentioning
confidence: 52%
“…While the general activities of SKI606 and PP2 are similar, slight differences in affinity and selectivity may account for the varied effects reported here and elsewhere. More likely, variations in chemical inhibitor results may take their origins in IVM culture protocols and/or differences in mouse strains used since mouse strain variations have been reported for both in vivo and in vitro matured oocytes (Ibanez et al, 2005a; Ibanez et al, 2005b). Additionally, Zheng and colleagues (2007) cultured naked oocytes in basal M2 medium without supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Although two recent studies performed in-depth analysis of allelic gene expression during embryonic development, these studies focused on much later stages (from E9.5 onward) [11,20]. Furthermore, previous studies were carried out on a variety of mouse genetic backgrounds, which is known to influence the efficiency of ESC derivation and to affect NT and PGA [29][30][31][32]. In our study, we make use of isogenic F1 hybrids of C57BL/6J (maternal) and DBA/2J (paternal) mouse inbred strains, previously also referred to as B6D2F1, B6D2 or BDF1.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we make use of isogenic F1 hybrids of C57BL/6J (maternal) and DBA/2J (paternal) mouse inbred strains, previously also referred to as B6D2F1, B6D2 or BDF1. This cross has been shown to be relatively efficient in NT and PGA, and the use of isogenic tissues and cell lines eliminates complications arising from strain-specific differences in gene expression [30,31,33]. Importantly, when derived from hybrid F1 mice, ESC-PGAs contain a mosaic homo-and heterozygous genotype due to chromosomal crossover occurring in the parental B6D2F1 oocyte during meiosis [10].…”
Section: Introductionmentioning
confidence: 99%